Disparitas Literasi Lingkungan Siswa Sekolah Dasar di Kota Bogor - Fiqri Nugraha*; Anna Permanasari; Indarini Dwi Pursitasari (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
Enviromental preservation plays an important role in the sustainability of living ecosystems. Environmental damage is caused by irresponsible human behavior so that environmental damage enters a very concerning stage. Therefore, environmental literacy needs to be developed from an early age in elementary school students as candidates for future generations who act as active agent of change. This is done with various effort through the educational process and begins with filtering information about student environmental literacy disparities, especially in Bogor City based on environmental schools and public schools. In this study using a survey method, using purposive random sampling technique. The population in this study was determined based on the category of environmental schools (SBL) and public schools (SU). Then, from the school category, respondents were selected based on the grade level. The high class level categories are grade 5 and 6, while the low class level categories are grade 3 and 4. Based on the analysis of the result of the answers to questionnaire, it was found that the environmental literacy of elementary school students in Bogor City for each school category has carried out environmental awareness activities. As for the measurement based on disposition toward the environment, the assessment of students environmental literacy was categorized as good, even among them very good for several indicators of environmental literacy.